The Relationship Between Pre-Service Training and Teaching Self-Efficacy for Inclusive Practices - Jennifer Francois (Educational Considerations, 2020)
Pre-service programming is instrumental in providing skills to teachers that builds positive teaching self-efficacy. This becomes increasingly important for those teachers who are hired to work in inclusive settings. Directives by the Division for Early Childhood and the Individuals for Disabilities Act have outlined content areas that teachers working in special education settings should have knowledge of and are comfortable in implementing (Division of Early Childhood 2014; United States Department of Education 2017). Many teachers, however, continue to come away from pre-service experiences without these skills (Lewis et al. 1999). Institutions continue to struggle with the integration of course content and curriculum around early intervention (Cochran et al. 2012; Stayton, Whittaker, Jones, & Kersting 2001). The purpose of this study is two-fold: 1) to examine the relationship between teaching self-efficacy for inclusive practices and perceptions of pre-service preparation and 2) to determine of perceptions of pre-service preparation predict measures of teaching self-efficacy for inclusive practices. A random sample of 250 licensed teachers from a Kansas were surveyed, 62 responded and 27 were included in the analyses. Results indicated that perceptions of pre-service preparation were related to overall teaching self-efficacy and measures of competence, not confidence.
Keywords: Teacher Training; Inclusion; Self-Efficacy